Relationship Between Mother's Characteristics and Husband's Support with the Use of Post-Partum Family Planning in Mamuju District - Mahardany, Beauty Octavia; Supriadi, Rizky Febriyanti (Politeknik Kesehatan Kemenkes Mamuju, 2023)
The application of Postpartum Family Planning is very important because the return of fertility to the mother after giving birth is unpredictable and can occur before the arrival of the menstrual cycle even in breastfeeding women. However, the KBPP coverage figures in Indonesia are still not satisfactory. Based on data from the 2019 Indonesia Health Profile, the coverage of KBPP in Indonesia has only reached 35.1%, while the coverage of using KBPP in West Sulawesi Province only reached 20%. The decision to use postpartum family planning for postpartum mothers is influenced by several factors, including the characteristics of the mother (education level, economic status, distance from home to health facilities) and husband's support. The purpose of this study was to analyze the relationship between mother's characteristics and husband's support for the use of postpartum family planning in Mamuju Regency. The method used is a quantitative method with a cross sectional approach. Sampling used a purposive sampling technique according to the inclusion and exclusion criteria. The sample used was 400 postpartum mothers in Mamuju Regency. The dependent variable is the use of KBPP and the independent variable is the characteristics of the mother and husband's support. The type of data analysis used was the contingency coefficient C test. The results showed that there was a significant relationship between economic level, distance from home to health facilities and husband's support for the decision to use postpartum family planning (p <0.05). Conclusion: there is a statistically significant relationship between the characteristics of the mother which includes economic status, distance to health facilities and husband's support for the use of Postpartum Family Planning in Mamuju District